Non-invasive assessment of proarrhythmic risks associated with isoprenaline and the dietary supplement ingredient synephrine using human induced pluripotent stem cell-derived cardiomyocytes - Yuan, Xin; Yu, Tingting; Zhang, Zhang; Li, Sen (Frontiers in Cardiovascular Medicine, 2024)
Background There have been conflicting reports about the proarrhythmic risk of p-synephrine (SYN). To address this, human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) combined with the microelectrode array (MEA) system have been utilized to assess arrhythmia risks, particularly in the context of adrenomimetic drugs. Aim This study aims to determine whether MEA recordings from hiPSC-CMs could predict the proarrhythmic risk of adrenomimetic drugs and to investigate the cardiovascular effects and mechanisms of SYN. Materials and methods We employed MEA recordings to assess the electrophysiological properties of hiPSC-CMs and conducted concentration-response analyses to evaluate the effects of SYN and Isoprenaline (ISO) on beating rate and contractility. A risk scoring system for proarrhythmic risks was established based on hiPSC-CMs in this study. ISO, a classic beta-adrenergic drug, was also evaluated. Furthermore, the study evaluated the risk of SYN and recorded the concentration-response of beating rate, contractility and the change in the presence or absence of selective β1, β2 and β3 adrenergic blockers. Results Our results suggested that ISO carries a high risk of inducing arrhythmias, aligning with existing literature. SYN caused a 30% prolongation of the field potential duration (FPD) at a concentration of 206.326 μM, a change significantly different from baseline measurements and control treatments. The half maximal effective concentration (EC50) of SYN (3.31 μM) to affect hiPSC-CM beating rate is much higher than that of ISO (18.00 nM). The effect of SYN at an EC50 of 3.31 μM is about ten times more potent in hiPSC-CMs compared to neonatal rat cardiomyocytes (34.12 μM). SYN increased the contractility of cardiomyocytes by 29.97 ± 11.65%, compared to ISO's increase of 50.56 ± 24.15%. β1 receptor blockers almost eliminated the beating rate increase induced by both ISO and SYN, while neither β2 nor β3 blockers had a complete inhibitory effect. Conclusion The MEA and hiPSC-CM system could effectively predict the risk of adrenomimetic drugs. The study concludes that the proarrhythmia risk of SYN at conventional doses is low. SYN is more sensitive in increasing beating rate and contractility in human cardiomyocytes compared to rats, primarily activating β1 receptor.